VD_FINDINFO Décision / 2020 / 571 vom 22. Juli 2020 - VD Tribunal cantonal (2020)
DROIT D'ÊTRE ENTENDU, DÉFENSE D'OFFICE, RÉPARATION DU VICE DE PROCÉDURE | 29 al. 2 Cst., 132 CPP (CH), 3 al. 2 let. c CPP (CH)